Flow-less and shape-conformable CNT sheet nanogenerator for self-powered motion sensor. Issue 37 (12th September 2016) - Song, Hyelynn; Kim, Taewoo; Im, Hyeongwook; Ovalle-Robles, Raquel; Kang, Tae June; Kim, Yong Hyup
Abstract : A carbon nanotube (CNT) sheet nanogenerator that does not require any liquid or gas flow for power generation is developed on the basis of Coulombic interactions, making the device attractive as a building block for self-powered sensors. Abstract : A carbon nanotube (CNT) sheet nanogenerator that does not require any liquid or gas flow for power generation is developed on the basis of Coulombic interactions, making the device attractive as a building block for self-powered sensors. The working principle of the CNT nanogenerator is probed in terms of sweeping speed, distance between charged object and nanotube sheet, surface charge, and number of layers of nanotube sheet. The nature of the CNT sheet and its formation process is such that simply winding the CNT sheet stripe n times around a substrate leads to increasing the power n times. For a practical demonstration of the CNT nanogenerator, a self-powered sensor array screen is developed that can read finger movements, just as with a finger command on a smartphone screen.